Self-healing keratin-based cryogel: A pharmaceutical-free, biomaterial for wound healing, antibacterial protection, and regenerative therapeutics - Syed Waqas Ali Shah; Hao Yuan; Shaohao Quan; Guifang Pan; Xingxing Li; Huiling Shen; Hanhan Xie; Jundong Shao (Materials & Design)
Multidrug-resistant (MDR) bacterial infections in chronic wounds pose a serious clinical challenge, necessitating innovative, drug free therapeutic strategies. Here, we report a novel self-healing keratin-based cryogel (KGG), fabricated via cryo-polymerization using keratin (KR), gum arabic (GA) and glycerol (GC). Unlike conventional hydrogels requiring antibiotics or growth factors, KGG demonstrates intrinsic regenerative, antibacterial, antioxidant, and hemostatic properties. Its highly interconnected macroporous structure, shape-memory behavior, and superior absorbency enable efficient exudate management and cellular infiltration. The cationic KR network facilitates electrostatic interactions with bacterial membranes, providing strong antibacterial activity against Escherichia coli (E. coli) and Methicillin-Resistant Staphylococcus aureus (MRSA) without promoting resistance. Additionally, KGG scavenges reactive oxygen species (ROS), modulates immune responses, and promotes macrophage polarization creating a pro-healing environment. In vitro and in vivo studies confirm its non-cytotoxic, enhanced angiogenesis, accelerated re-epithelialization, and inflammation suppression. The cryogel also exhibits excellent hemostatic performance, making it suitable for hemorrhage control. These finding highlight KGG as a multifunctional, pharmaceutical free platform for treating MDR-infected chronic wounds, with added potential in trauma care applications.